Rationalizing and Disrupting Fluxional Processes in Agostically Stabilized 14‐Electron Alkyliridium Hydride Complexes. Issue 28 (11th August 2014) - Phillips, Nicholas; Treasure, Lucinda; Rees, Nicholas H.; Tirfoin, Rémi; McGrady, John E.; Aldridge, Simon
Abstract: We have investigated the fundamental patterns of reactivity for the cationic Ir III complexes [(6‐Mes)(6‐Mes′)Ir(H)] + and [(7‐Mes)(7‐Mes′)Ir(H)] + [6‐Mes, 7‐Mes = ring‐expanded N‐heterocyclic carbene (NHC) ligands, ′ indicates that NHC is tethered through an iridium‐bound CH2 group], each of which undergoes degenerate fluxional exchange between an iridium‐bound agostic C–H bond and the discrete alkyl/hydride ligands resulting from C–H activation. A comparison between the activation parameters Δ H ‡ and Δ S ‡ determined by variable‐temperature NMR (VT‐NMR) spectroscopy line‐shape analysis and those obtained from DFT calculations on model systems offers a basis to discriminate between different possible exchange mechanisms, and an oxidative addition pathway gives the lowest barrier and also the best agreement between experiment and theory. The addition of neutral Lewis base donors to [(6‐Mes)(6‐Mes′)Ir(H)] + resulted in the displacement of the weak agostic C–H··· Ir interaction and the generation of static (alkyl)iridium(III) hydride complexes such as [(6‐Mes)(6‐Mes′)Ir(H)(CN t Bu)2 ] + . The analogous carbonyl complex is more labile, with the enhanced π‐acceptor properties of the ancillary ligands leading to C–H reductive elimination and to the formation of the Ir I complex [(6‐Mes)2 Ir(CO)2 ] +, which incorporates unactivated NHC donors and has the ability to reversibly take up H2 . Abstract : By NMR spectroscopy and DFT methods, the mechanism of fluxional exchange in cationic bis(NHC) Ir III systems with an agostic C–H bond and cis ‐alkyl/hydride ligands is shown to feature an oxidative pathway. Related nonfluxional systems can be "trapped" by the addition of two‐electron donors (L), and their stability to C–H reductive elimination can be tuned through the π‐acceptor properties of L.